ANALISIS PENGARUH PEMAHAMAN, PENERAPAN SELF ASSESMENT SYSTEM PADA KEPATUHAN WPOP DALAM MELAKSANAKAN PELAPORAN SPT DI KPP PRATAMA PURWOREJO - , (Politeknik Sawunggalih Aji, 2023)
The Self Assessment System tax collection system is one of the government's efforts to make it easier for taxpayers to submit annual tax returns. Self Assessment System, namely a tax collection system that imposes the determination of the amount of tax that needs to be paid by the taxpayer concerned independently. Taxpayers are parties that play an active role in calculating, paying, and reporting the amount of tax to the Tax Service Office (KPP). The population and sample in this study are individual taxpayers in Purworejo Regency. The sampling technique used in this study is a random sampling technique. The sample of this research is 100 respondents. The data collection method used is primary data using a questionnaire. Multiple linear regression analysis technique. The results of this study based on the analysis carried out, it can be concluded that the understanding of the self-assessment system and the application of the self-assessment system has an R-Square value of 0.480. The understanding of the self-assessment system has a positive and significant effect on individual taxpayer compliance with a significant value of 0.001 and the implementation of the self-assessment system also has a significant effect on individual taxpayer compliance with a significant value of 0.001. The understanding and application of the self-assessment system simultaneously affects the level of compliance of individual taxpayers with a significance value of 0.000.